Catheter Ablation for Supraventricular Tachycardia in Infants: A Systematic Review and Selective Meta‐Analysis - Karin Vasic; Aleksandar Markovic (Pacing and Clinical Electrophysiology, 2026)
ABSTRACT Background Supraventricular tachycardia (SVT) is the most common clinically significant arrhythmia in infancy. Although pharmacological therapy is the first‐line treatment, catheter ablation may be considered in drug‐refractory or life‐threatening cases. We systematically reviewed the literature and performed a meta‐analysis to evaluate the reported efficacy and safety of catheter ablation for SVT in infants (≤12 months). Methods A systematic search of PubMed/MEDLINE, Embase, and Scopus was conducted from inception to January 2026 in accordance with PRISMA guidelines. Studies reporting catheter ablation outcomes in infants were included. Five studies met the eligibility criteria for qualitative synthesis. One case report was excluded from quantitative analysis according to prespecified criteria, leaving four studies comprising 57 infants. A single‐arm random‐effects model was used to estimate pooled acute procedural success, complications, and arrhythmia recurrence. Results The pooled acute procedural success rate was 93% (95% CI 84%–98%; I 2 ≤5%). The pooled complication rate was 7% (95% CI 3%–17%; I 2 ≤5%). No permanent atrioventricular block or procedure‐related deaths were reported. Arrhythmia recurrence occurred in 9% of infants (95% CI 4%–19%) during 6–24 months of follow‐up. Conclusion Catheter ablation for SVT in infants is associated with high reported procedural success and low reported complication rates when performed in experienced pediatric electrophysiology centers. However, conclusions are limited by the small number of highly selected observational studies and potential publication and referral bias. Available evidence is limited, highlighting the need for larger prospective multicenter studies to better define patient selection, optimal timing, and long‐term outcomes.